Uma proposta de alfabetização e letramento no contexto da educação indigena - Souza, Marinez Silva Santos (2024)
The present dissertation, part of the project "Digital Social Networks and Education" within the research group named "New Teaching and Learning Technologies," aimed to provide a didactic resource geared towards school Physical Education teachers. This resource includes a selection of joint mobility exercises available on the social media platform Instagram, seeking to solve the problem of how to use Instagram effectively in physical education classes. The proposal aims to offer a sequence of joint mobility exercises that can be used as a didactic resource through the Instagram social network. The qualitative research addresses the theory of Historical-Cultural as an educational theory, establishing connections with Physical Education practices. We then discuss the history of Physical Education in Brazil, highlighting different trends and approaches over time, aiming to understand its cultural transformations and associated practices. Subsequently, we discuss the structure of Physical Education in the National Common Curricular Base (BNCC), with an emphasis on the gymnastics thematic unit due to its central role as a starting point for exploring joint mobility. We present a study of the state of knowledge about the applications that have been used in school Physical Education classes. Finally, we explore some of the resources offered by Instagram, with the aim of showcasing its potentialities, encouraging its use as an educational tool. We consider that digital technologies, if used in a structured and critical manner, can be useful in the daily lives of teachers in general, meeting the demands involved in digital technological aspects of the 21st century, facilitating the teaching-learning process.